2020
DOI: 10.1371/journal.pone.0231608
|View full text |Cite
|
Sign up to set email alerts
|

Equine Facial Action Coding System for determination of pain-related facial responses in videos of horses

Abstract: During the last decade, a number of pain assessment tools based on facial expressions have been developed for horses. While all tools focus on moveable facial muscles related to the ears, eyes, nostrils, lips, and chin, results are difficult to compare due to differences in the research conditions, descriptions and methodologies. We used a Facial Action Coding System (FACS) modified for horses (EquiFACS) to code and analyse video recordings of acute short-term experimental pain (n = 6) and clinical cases expec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(69 citation statements)
references
References 24 publications
5
63
1
Order By: Relevance
“…Rashid et al . [ 33 ] found that nostril dilator (AD38) and chin raiser (AU17) were indicative of pain when using both the HFI and Co-occurrence methods. The fact that nostril dilator (AD38) is also present during stressful management conditions could indicate that this AD is common during simple management interventions and less significant for determining pain.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Rashid et al . [ 33 ] found that nostril dilator (AD38) and chin raiser (AU17) were indicative of pain when using both the HFI and Co-occurrence methods. The fact that nostril dilator (AD38) is also present during stressful management conditions could indicate that this AD is common during simple management interventions and less significant for determining pain.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the relative temporal distribution of AUs was also considered. In order to do this, the method of Rashid et al [ 33 ], here referred to as the Co-occurrence method, was used to calculate the co-occurrence of AUs. This method selected EquiFACS codes that occurred together with other EquiFACS codes more frequently in stress than in no-stress states.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations